One-step synthesis of FeO(OH) nanoparticles by electric explosion of iron wire underwater - Hao Yin; Xin Gao; Peng-wan Chen (Defence Technology, 2022)
In this study, we investigated electric explosion of iron wire in distilled water with different energy input adjusted by charging voltage. The as-prepared samples were characterized by X-ray diffraction (XRD), scanning electron microscopy (SEM), transmission electron microscopy (TEM) and X-ray photoelectron spectroscopy (XPS), showing the presence of iron and multiple iron-based compounds oxides with contents influenced by the experimental conditions. In particular, pure FeO(OH) nanoparticles were obtained using electric explosion of iron wire with energy input of 1125 J at charging voltage of 15 kV. Analysis of discharge current and resistive voltage data indicate that the high energy input induced by strong plasma discharge at high charging voltage is a key factor to form FeO(OH). This study presents a one-step method to synthesize FeO(OH) nanoparticles using electric explosion of iron wire.